Addressing Structural Inequities, a Necessary Step Toward Ensuring Equitable Access to Telehealth for Medication Abortion Care During and Post COVID-19 - Thompson, Terri-Ann; Northcraft, Dana; Carrión, Fabiola (Frontiers in Global Women's Health, 2022)
Telehealth, one of the newest health innovations, has been promoted as a tool to enhance access to health care services in ways that center patient needs. However, integrating telehealth within an inequitable health system undermines its potential. This perspective highlights policies and practices that foster structural inequities and names their impact on the use and acceptability of telehealth for medication abortion among specific communities of color. Communities of color have a higher prevalence of abortion use but face many barriers, including financial and geographic barriers, to abortion access. Preliminary evidence on telehealth for medication abortion shows that it is highly acceptable, accommodating of patient needs, and may allow patients to access abortion care at earlier gestational ages. However, evidence during the COVID-19 pandemic shows that utilization of telehealth is lower among communities of color. We describe how systemic barriers, including regulations on or laws banning telehealth for medication abortion, disinvestments in digital access, and restrictions on public insurance coverage, could perpetuate lower utilization of telehealth for medication abortion care among communities of color. We call for systems changes that will remove these barriers and make this health care innovation available to all who may desire it.